Central composite design for the advanced treatment of biologically treated leachate nanofiltration concentrate using zero-valent copper and iron activated persulfate - Varank, Gamze; Guvenc, Senem Yazici; Cebi, Aleyna; Guven, Emine Can (ELSEVIER SCIENCE INC, 2020)
The purpose of this study was to investigate chemical oxygen demand (COD) removal from leachate nanofiltration concentrate with high resistant organic matter content by persulfate (PS) oxidation in which zero-valent copper (ZVCu) and zero-valent iron (ZVI) are used as activators. Within the scope of the study, response surface methodology (RSM) was applied to determine the optimum operating conditions by which maximum COD removal efficiency would be obtained, and effects of independent variables (pH, PS concentration, dosage of ZVI and ZVCu, reaction time) on COD removal efficiency and their interaction with each other were determined. The degree of significance of each independent variable was determined by analysis of variance. Estimated COD removal efficiencies under optimum conditions determined by the model were found to be 36.48% and 47.15%, respectively, for ZVCu-activated PS (ZVCu/PS) and ZVI-activated PS (ZVI/PS) processes whereas experimental removal efficiencies were 34.29% and 45.56%, respectively, for ZVCu/PS and ZVI/PS processes. The results of the study indicated that ZVI and ZVCu activated PS oxidation is effective and economic for COD removal from leachate nanofiltration concentrate with the BOD5/COD ratio of 0.042, and RSM is a suitable method for the design and optimization of both processes.
Keywords: Leachate nanofiltration concentrate; ZVCu; ZVI; Persulfate oxidation; CCD; RESPONSE-SURFACE METHODOLOGY; PETROCHEMICAL WASTE-WATER; ADVANCED OXIDATION PROCESS; DISSOLVED ORGANIC-MATTER; LANDFILL LEACHATE; ELECTROCHEMICAL ACTIVATION; HYDROGEN-PEROXIDE; EFFICIENT REMOVAL; FENTON OXIDATION; AQUEOUS-SOLUTION; Engineering; Water Resources